KOMPETENSI ABSOLUT PERADILAN AGAMA Analisis Historis-Normatif dari Zaman Kerajaan sampai Reformasi - Mustaufikin Mustaufikin (LPPM IAI Hasanuddin Pare-Kediri, 2017)
The existence of the Religious Courts has indeed been recognized by the existence of Law Number 14 of 1970 concerning the Basic Provisions of Judicial Power. After the enactment of Law Number 1 of 1974 concerning Marriage, it began to provide a juridical basis for the competence of the Religious Courts, the law regulates marriage, which includes divorce, determination of the legitimacy of children, guardianship, determination of the origin of children, and marriage permits. third is the development of the Religious Courts, namely the development of absolute competence of the Religious Courts. The search will start from the time of the kingdom until the reformation era, precisely when Law No. 3 of 2006 was issued regarding amendments to Law No. 7 of 1989 concerning the Religious Courts. Therefore, the approach used in this study is a historical approach, to find out